2008
DOI: 10.1080/08860220701742047
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education: An Efficient Adjuvant Therapy for Hyperphosphatemia in Hemodialysis Patients

Abstract: Patient education could be helpful and efficient in hyperphosphatemic control in dialysis patients. The patient education should be given before the serum iPTH level getting high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…An earlier study also reported the same finding (31). Comfort-based interventions may improve psychospiritual and environmental conditions of patients because these interventions help patients feel that nurses are supporting them, caring for them, and attempting to alleviate their problems and improve their comfort.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…An earlier study also reported the same finding (31). Comfort-based interventions may improve psychospiritual and environmental conditions of patients because these interventions help patients feel that nurses are supporting them, caring for them, and attempting to alleviate their problems and improve their comfort.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, other studies reported that back massage alleviates the effects of discomforting factors such as pain, nausea, itching, and muscle cramps (5,36,37). The positive effects of back massage are attributed to the improvements in blood flow and lymphatic drainage, reduction of serum cortisol level, and increases in serum serotonin and dopamine levels (5,20,28,31,36,37). As an inexpensive and noninvasive complementary modality, massage can also facilitate patient care and improve nursepatient communication (37).…”
Section: Discussionmentioning
confidence: 99%
“…Hörl used an individual and flexible approach with his patients and concluded that this method is more efficacious (18) . Another study reduced levels of phosphorus when intensive and individualized care was applied (19) . In this study, the patients were considered apt after obtaining 100% of correct answers in the evaluation questionnaire; the educational meetings of 30 minutes were kept until they achieved this mark (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reduced levels of phosphorus when intensive and individualized care was applied (19) . In this study, the patients were considered apt after obtaining 100% of correct answers in the evaluation questionnaire; the educational meetings of 30 minutes were kept until they achieved this mark (19) . In this study, guidance was provided to small groups; teaching was not individualized.…”
Section: Discussionmentioning
confidence: 99%
“…Few medical staff or nurses have additional qualifications in teaching, yet there seems little doubt that time spent with the patient is beneficial and several studies have shown that patient education programs are associated with an improvement in serum phosphate control, [92][93][94] although repeated reinforcement is required. 95 Most adults are aware of the importance of controlling blood pressure, cholesterol, and body mass index, even if they do not have any illness. However, they are very unlikely to have come across any public health messages concerning phosphate, and therefore it is incumbent on the CKD team to provide appropriate education.…”
Section: Patient Education To Assist Control Of Serum Phosphatementioning
confidence: 99%